Global, regional, and national impact of Down syndrome on child and adolescent mortality from 1980 to 2021, with projections to 2050: a cross-sectional study - Ye, Erdengqieqieke; Wu, Erman; Han, Rui (Frontiers in Public Health, 2025)
IntroductionDown syndrome, resulting from trisomy 21, is a prevalent genetic disorder. Despite improvements in life expectancy and quality of life due to medical progress, children and adolescents (under the age of 20 years) with Down syndrome still face higher mortality rates. Future research is essential to elucidate the epidemiological patterns and trends in Down syndrome among children and adolescents, enabling the development of effective prevention and intervention strategies to improve survival and health outcomes.MethodsThis study draws on Global Burden of Disease (GBD) 2021 mortality data for children and adolescents with Down syndrome. Pearson’s correlation coefficient was leveraged to assess the relationship between Down syndrome mortality and the Socio-demographic Index (SDI). The estimated annual percentage change (EAPC) in mortality was calculated to track temporal trends, and the Bayesian age-period-cohort (BAPC) model was employed to forecast future mortality.ResultsOver the past 42 years, there have been fluctuations in mortality among children and adolescents with Down syndrome. Globally, deaths have decreased by 22.8% from 26.95 thousand (95% uncertainty interval [UI], 10.10–74.66 thousand) in 1980 to 20.81 thousand (95% UI, 14.18–36.49 thousand) in 2021. Furthermore, BAPC model projections indicate a sustained reduction in mortality for children and adolescents with Down syndrome. Predominantly, deaths occur in 0–4 age group, with higher death rates in Low SDI regions, and notably, the number and rate of female patients exceed those of male patients. Intriguingly, a negative correlation was observed between death rates and higher SDI.ConclusionMost countries have seen a decline in Down syndrome deaths among children and adolescents over the last 42 years, but a few high SDI countries are witnessing an increase. Future health interventions should prioritize these countries, focusing on resource allocation, infrastructure, and health education. Continued efforts on care for the 0–4 age group with Down syndrome are crucial to further reducing deaths in this age group.